2018
DOI: 10.1128/jb.00701-17
|View full text |Cite
|
Sign up to set email alerts
|

A Quorum Sensing-Regulated Protein Binds Cell Wall Components and Enhances Lysozyme Resistance in Streptococcus pyogenes

Abstract: The Rgg2/3 quorum sensing (QS) system is conserved among all sequenced isolates of group A (GAS;). The molecular architecture of the system consists of a transcriptional activator (Rgg2) and a transcriptional repressor (Rgg3) under the control of autoinducing peptide pheromones (SHP2 and SHP3). Activation of the Rgg2/3 pathway leads to increases in biofilm formation and resistance to the bactericidal effects of the host factor lysozyme. In this work, we show that deletion of a small gene, , abolished both phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 51 publications
(65 reference statements)
2
30
0
Order By: Relevance
“…Cytochrome C assay was performed as described previously (55,56) with minor modifications. Briefly, overnight cultures of strains were diluted to an OD 600nm of 0.05 in 20 mL prewarmed THB, with no antibiotic, and grown to mid exponential phase (OD 600nm between 0.48 – 0.6) before cells were pelleted to an OD 600nm of 7 in 1 mL and washed twice with morpholinepropanesulfonic acid (MOPS) at pH 7.…”
Section: Methodsmentioning
confidence: 99%
“…Cytochrome C assay was performed as described previously (55,56) with minor modifications. Briefly, overnight cultures of strains were diluted to an OD 600nm of 0.05 in 20 mL prewarmed THB, with no antibiotic, and grown to mid exponential phase (OD 600nm between 0.48 – 0.6) before cells were pelleted to an OD 600nm of 7 in 1 mL and washed twice with morpholinepropanesulfonic acid (MOPS) at pH 7.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work illustrated that cell surface properties of GAS are altered via Rgg2/3 QS. 3,4,14 To examine if these surface changes include alterations of the repertoire or display of antigens, macrophages were infected with GAS inactivated by different methods, including heat (heat killed, HK), short wave ultraviolet light (UV), and 4% paraformaldehyde (PFA) treatment. While heat has been shown to alter cell wall peptidoglycans and denature proteins, UV treatment damages DNA and RNA and is less likely to interfere with cell surface properties.…”
Section: Suppression Requires Contact With Live Qs-on Gasmentioning
confidence: 99%
“…3 We previously described that activation of Rgg2/3 QS mediates production of biofilms and resistance to the host antimicrobial factor lysozyme, two phenotypes that rely on surface modifications and were shown to require QSregulation of StcA. 3,4 We wondered whether regulation of StcA also enabled suppression of inflammatory pathways in innate immune cells. Infecting macrophages with 0414c and 0450-0460 grown in the presence of SHP (QS-ON) or inactive revSHP (QS-OFF) showed that while spy49_0414c is not required for QS-regulated attenuation of cytokine responses, spy49_0450-0460 is required (Fig 5C).…”
Section: A Qs-regulated Operon Is Required For Cytokine Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the earliest reports of population-density regulation of bioluminescence in Vibrio fischeri and competence in Streptococcus pneumoniae, we now appreciate that many virulence functions are also regulated via quorum sensing signaling cascades. In this issue of JB, Gogos et al describe a quorum sensing-regulated protein that affects the cell wall and enhances lysozyme resistance of Streptococcus pyogenes (29). Hustmyer et al introduce a new method, rapid arbitrary PCR insertion libraries (RAIL), to define the promoter regions important to acyl homoserine lactone-regulated functions in Vibrio harveyi (30) (see also the accompanying commentary by Matson describing RAIL and its potential for other researchers [31]).…”
mentioning
confidence: 99%